PARENTING COMMUNICATION IN A PANDEMIC (DESCRIPTIVE STUDY OF PARENTING COMMUNICATION IN EDUCATING AND PROTECTING CHILDREN DURING A PANDEMIC IN GIRI MEKAR VILLAGE, CILENGKRANG DISTRICT, BANDUNG REGENCY) - Aulia Asmarani (Dinasti International Journal of Education Management And Social Science, 2022)
The purpose of this study was to find out how the description of parenting communication in educating and protecting children during the pandemic, especially in Giri Mekar Village, Cilengkrang District, Bandung Regency, and the general pattern of parenting communication that occurred during the covid 19 pandemic. The research locus was chosen based on the relationship with the community. The author formed the study as part of community service activities going on for approximately 3 years. The author wants to know for sure in advance and explore parenting communication that occurs so that steps for PKM activities can be taken like what is useful and effective according to the needs of students, parents, schools, and the community in general. This study uses a qualitative descriptive research method. By triangulating sources, The researcher used the Principal of SD Negeri Girimekar 3, the supervising teacher for the students whose parents were the respondents, and the class teacher. This research is based on the reason that the students of SD Negeri Girimekar 3 are many participants in the author's learning home learning community (PKBM). The study results found that not only teachers but also parents also act as the first and primary educators. The latter has the responsibility to create and nurture their children to become good children in terms of behavior, mental, and heart. Responsibility as a parent must motivate their children to become disciplined and confident children using their potential. The attitude of the mother and father towards the child will greatly affect how the child's temperament or behavior in his daily life.